2020
DOI: 10.1155/2020/9513576
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal Enhancement due to Neurosarcoidosis Mimicking Malignancy

Abstract: The present report describes the case of a 56-year-old African American man experiencing progressive disequilibrium, lower extremity weakness, difficulty walking, and hearing loss. Brain magnetic resonance imaging showed leptomeningeal enhancement. Initial differential diagnosis was broad, including malignant, infectious, and inflammatory etiologies. The cerebrospinal fluid analyses demonstrated lymphocytic pleocytosis, hypoglycorrhachia, and hyperproteinorrachia but no other abnormalities. An extensive infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Saltijeral et al have described a case of NS with leptomeningeal enhancement mimicking malignancy, similar to the patient in this case report. 9 ) Furthermore, Deguchi et al have reported a case of NS requiring differentiation from tuberculous meningitis. 10 ) Based on the finding by Kidd et al, who have reported that 14% and 40% of the patients with NS had pachymeningeal and leptomeningeal lesions, respectively, 2 ) NS can have pachymeningeal and leptomeningeal lesions mimicking malignant tumors or other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Saltijeral et al have described a case of NS with leptomeningeal enhancement mimicking malignancy, similar to the patient in this case report. 9 ) Furthermore, Deguchi et al have reported a case of NS requiring differentiation from tuberculous meningitis. 10 ) Based on the finding by Kidd et al, who have reported that 14% and 40% of the patients with NS had pachymeningeal and leptomeningeal lesions, respectively, 2 ) NS can have pachymeningeal and leptomeningeal lesions mimicking malignant tumors or other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the diagnosis of LM mainly relies on MRI and cerebrospinal fluid (CSF) cytology, but their sensitivity is low ( 6 , 7 ). MRI findings of various diseases involving the leptomeningeal structures are similar to those of LM, with little distinctive capacity between some diseases and LM ( 8 , 9 ). CSF cytology remains the gold standard for the diagnosis of LM.…”
Section: Introductionmentioning
confidence: 95%
“…Various diseases may present with leptomeningeal involvement, mimicking LMD. Currently, these have been sparsely described in the literature, primarily in the context of case reports, including rare instances of neuroborreliosis, giant cell arteritis, and sarcoidosis [ 148 , 149 , 150 ].…”
Section: Leptomeningeal Mimicsmentioning
confidence: 99%